Asuhan Keperawatan Pada Pasien Dengan Tuberkulosis Paru Di Ruang Rawat Inap Paru Rsud Prof H. Muhammad Yamin, Sh Pariaman - Gisca Juwinanda Putri; Mike Asmaria; Kheniva Diah Anggita; Aulia Asman (CV. ITTC INDONESIA, 2026)
Pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis and is one of the ten leading causes of death worldwide. Globally, there are an estimated 10.8 million cases of pulmonary tuberculosis in 2023. Based on the 2022 Health Profile in Indonesia, the incidence of pulmonary tuberculosis is 368,337 cases. At the provincial level, West Sumatra recorded 3,093 cases of tuberculosis in 2023, while Pariaman City recorded 45 cases of pulmonary tuberculosis in 2025. Locally, Prof. Muhammad Yamin, SH, Pariaman Regional General Hospital experienced a decrease in the number of cases from 69 cases in 2024 to 45 cases in 2025. This study aims to describe nursing care for Mrs. I, 66 years old, who was diagnosed with pulmonary tuberculosis. The case study method was used through five stages of the nursing process: assessment, diagnosis, intervention, implementation, and evaluation. Nursing problems found included ineffective airway clearance, ineffective breathing patterns, diarrhea, nutritional deficits, disturbed sleep patterns, and activity intolerance. Nursing interventions carried out included oxygen administration, effective cough education, nutritional and fluid monitoring, and support for independence in daily activities. The evaluation showed significant clinical improvement. The results of this study emphasize the importance of comprehensive and continuous nursing care in the management of pulmonary tuberculosis. Patients are advised to adhere to the recommended treatment regimen, maintain personal and environmental hygiene, avoid smoking, consume nutritious foods, and undergo regular check-ups at healthcare facilities to optimize the healing process and prevent transmission to others